Lifetime income and old age mortality risk in Italy over two decades - Michele Belloni; Rob Alessie; Adriaan Kalwij; Chiara Marinacci (Demographic Research, 2013)
Background: The evidence on the shape and trend of the relationship between (lifetime) income and old age mortality is scarce and mixed both for North American and European countries. Nationwide evidence for Italy does not exist yet. Objective: We investigate the shape and evolution of the association between lifetime income and old age mortality risk, referred to as the income-old age mortality gradient, for males in the 1980s and the 1990s. Methods: We use data drawn from an administrative pension archive and proxy individual lifetime income with pension income. We use non-standard Cox proportional hazard models, in which the positions and number of the knots in the spline function for income are determined by the data. Results: The income-old age mortality gradient is negative but weak across most of the income distribution. Ist shape shows two kink points situated almost at the same percentiles of the income distribution during the 1980s and the 1990s. The widening of the gradient over time is largely explained by regional differences in mortality and income. Conclusions: Our findings show that mortality risk decreases with income. Once regional differences are controlled for, the relative difference in mortality risk between high and low-income individuals in Italy is rather stable over time.